AI goes to work. - SCRIVEN, GUY (Economist, 2023)
The article focuses on the increasing adoption of generative artificial intelligence (AI) by different groups with an initial benefit for software developers and consumers in 2021-2023 and a shift towards technology giants in 2023. Topics include the evolving impact on share prices of major tech companies, the expected surge in enterprise adoption as companies outside the technology sector seek to cut costs and enhance productivity in 2024, and the factors driving this shift.